Pertanggungjawaban Pidana Pemalsuan Surat Domisili Pada Penerimaan Peserta Didik Baru Dengan Sistem Zonasi - Raehananda, I Gusti Ngurah Agung Deva Hade; Sari Harianto, Diah Ratna (Kertha Wicara : Journal Ilmu Hukum, 2020)
The purpose of this study is to examine the criminal liability of perpetrators of domicile mail forgery in the acceptance of new students with the zonation system as well as forms of funding for perpetrators of domicile mail forgery. This method of writing journals uses normative research based on primary legal materials that include applicable laws and regulations, secondary legal materials that include books and journals and using legal approaches and conceptual approaches. Normative legal research conducted to examine the void of norms in Regulation of the Minister of Education and Culture No. 44 of 2019 related to the arrangement of domicile letters as a substitute for a family card in the acceptance of new students with the zonation system. The results showed that perpetrators of domicile letter forgery in the college acceptance with zonation system can be held criminally liable if the perpetrator has fulfilled elements in criminal accountability and forms of funding for perpetrators of forgery of domicile letters is imprisonment for parents/guardians of students and new students who are over 18 years old, imprisonment and criminal fines if carried out by state officials. Diversion efforts for the perpetrator, namely potential of college acceptance participants who are minors. Keywords : Criminal liability, forgery, zonation system